Clinical analysis of 4 children with hereditary hypercholesterolemia - Hao, H M (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To investigate the clinical characteristics of hereditary hypercholesterolemia in childhood. Methods: The clinical data including general conditions, clinical manifestations, laboratory tests, and genetic testing results of 4 children with hereditary hypercholesterolemia who admitted to Henan Children's Hospital from January 2020 to December 2020 were retrospectively analyzed. Results: There were 4 female children aged 5.5,1.5,6.3,3.1 years, all presented with skin xanthoxoma as the chief complaint. Plasma total cholesterol (range 11.8 to 20.9 mmol/L) and low density lipoprotein-cholesterol (range 8.2 to 13.7 mmol/L) were significantly elevated. The serum β-glutamate levels in case 1 (241.2 μmol/L) and case 2 (164.2 μmol/L) increased significantly. Genetic analysis revealed compound heterozygous variants of ABCG8 gene in case 1 and ABCG5 gene in case 2 who were diagnosed with sitosterolemia. Case 3 and 4 who all had family history of hypercholesterolemia and compound heterozygous variants of LDLR gene were diagnosed with familial hypercholesterolemia. After diet treatment, the blood lipids returned normal and the skin xanoma subsided in case 1 and 2. In case 3 and 4, the blood lipids gradually decreased after diet and rosuvastatin treatment. Conclusions: Xanthomatosis is the common clinical manifestation of sitosterolemia and familial hypercholesterolemia. Family history, blood plant sterol profile, genetic variation, and changes in blood lipids after early dietary treatment are helpful for disease identification